Obesity following ART initiation is common and influenced by both traditional and HIV-/ART-specific risk factors. (2nd May 2018) - Bakal, David R; Coelho, Lara E; Luz, Paula M; Clark, Jesse L; De Boni, Raquel B; Cardoso, Sandra W; Veloso, Valdilea G; Lake, Jordan E; Grinsztejn, Beatriz
Abstract: Background: Obesity rates are increasing among HIV-infected individuals, but risk factors for obesity development on ART remain unclear. Objectives: In a cohort of HIV-infected adults in Rio de Janeiro, Brazil, we aimed to determine obesity rates before and after ART initiation and to analyse risk factors for obesity on ART. Methods: We retrospectively analysed data from individuals initiating ART between 2000 and 2015. BMI was calculated at baseline (time of ART initiation). Participants who were non-obese at baseline and had ≥90 days of ART exposure were followed until the development of obesity or the end of follow-up. Obesity incidence rates were estimated using Poisson regression models and risk factors were assessed using Cox regression models. Results: Of participants analysed at baseline ( n = 1794), 61.3% were male, 48.3% were white and 7.9% were obese. Among participants followed longitudinally ( n = 1567), 66.2% primarily used an NNRTI, 32.9% a PI and 0.9% an integrase strand transfer inhibitor (INSTI); 18.3% developed obesity and obesity incidence was 37.4 per 1000 person-years. In multivariable analysis, the greatest risk factor for developing obesity was the use of an INSTI as the primary ART core drug (adjusted HR 7.12, P < 0.0001); other risk factors included younger age, female sex, higher baseline BMI, lower baseline CD4+ T lymphocyte count, higher baseline HIV-1 RNA, hypertension and diabetes mellitus. Conclusions: Obesity following ART initiation is frequent among HIV-infected adults. Key risk factors include female sex, HIV disease severity and INSTI use. Further research regarding the association between INSTIs and the development of obesity is needed.